Dynamics of ungulates in relation to climatic and land use changes in an insularized African savanna ecosystem - Ogutu, Joseph O.; Owen-Smith, N.; Piepho, Hans-Peter; Kuloba, B.; Edebe, J. (Springer, 2012)
Land use change and human population growth are accelerating the fragmentation and insularization of wildlife habitats worldwide. The conservation and management of wildlife in the resultant 'island' ecosystems in the context of global warming is challenging due to the isolation and reduced size of the ecosystems and hence the scale over which ecosystem processes can operate. We analyzed trends in numbers of nine large herbivores in Kenya's Lake Nakuru National Park to understand how rainfall and temperature variability, surrounding land use changes, and boundary fencing affected wildlife population dynamics inside the park during 1970-2011. Buffalo, zebra and Thomson's gazelle numbers increased persistently. Grant's gazelle and impala increased initially then gradually declined. Waterbuck and warthog numbers progressively declined to levels that potentially threatened their local population persistence. The total biomass of ungulates tripled from 1970 to 2011, with buffalo replacing waterbuck as the predominant species in biomass. Increased competition from buffalo and zebra, heightened predation and illicit human harvests probably all contributed to the declines by waterbuck and warthog. Density-dependent limitation of population growth within the park confines was evident for buffalo, impala, eland, giraffe, Grant's and Thomson's gazelles. Fluctuations in the lake level related to varying rainfall affected changes in animal abundance through expansion of the lake area and flooding of grasslands bordering the lake. Unusually, the most stressful conditions were associated with high water levels following high rainfall. There was also evidence of carry-over effects from prior habitat conditions affecting all species. The relatively stable populations of all species except warthog and waterbuck demonstrate the remarkable capacity of this small, insularized park to retain viable populations of most of the large herbivores, without much management intervention.